Mein Louisiana-Leben : Werdegang eines Museums - Jensen, Knud W.; Louisiana Museum of Modern Art, Humlebaek (Klagenfurt : Ritter Verlag, 1991)
Alechinsky, Pierre ; Calder, Alexander ; Dali , Salvador ; Dubuffet , Jean ; Giacomette , Alberto ; Jensen , Vivi ; Klein , Yves ; Moore , Henry ; Picasso , Pablo ; Pollock , Jackson ; Sandber , Willem ; Tapies , Antoni ; Tinguely , Jean ; Toulouse - Lautrec , Henri de ; etc.
boek